Digital Marketing, Entrepreneurial Orientation, and Business Capital on the Financial Performance of MSMEs in Indonesia - Yuliastuti, Hilda; Putra, Johni Eka; Utomo, Bekti (IJBLE Scientific Publications Community Inc., 2024)
This study looks into how business capital, entrepreneurial orientation, digital marketing, and the financial performance of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia interact. The study analyzes data from a diverse sample of 400 MSMEs using Structural Equation Modeling with Partial Least Squares (SEM-PLS) 3 and a quantitative research design. Descriptive statistics shed light on the essential factors and demographic profile, and the measurement model assessment verifies the constructs' validity and reliability. Significantly positive correlations between digital marketing, entrepreneurial orientation, business capital, and financial success are established by the structural model study. The mediating roles of business capital and entrepreneurial orientation are revealed through indirect impacts. R-square values and model fit indices attest to the suggested model's resilience. The results add to our understanding of the variables that influence MSME success in the Indonesian business environment and provide useful information for future research projects, practitioners, and policymakers.